2021
DOI: 10.1080/20002297.2021.1964277
|View full text |Cite
|
Sign up to set email alerts
|

Profuse diversity and acidogenicity of the candida-biome of deep carious lesions of Severe Early Childhood Caries (S-ECC)

Abstract: Introduction: The retentive niches of deep caries lesions have a distinct biome. Methods: We evaluated the site-specific (occlusal and proximal) Candida -biome of Severe-Early Childhood Caries (S-ECC) in 66- children (132 lesions). Asymptomatic primary molars fitting the definition of the International Caries Detection and Assessment-(ICDAS)-caries-code 5/6 were analyzed. Deep-dentinal sampling and simultaneous assessment of pH were performed. Clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In terms of the predominant microbiota of dental caries, both streptococcal and lactobacillus genera have long been recognized to play a critical role, although recent work indicates clearly that fungi, predominantly Candida species, are prevalent in deep cavitated lesions [ 18 , 19 ]. Indeed, in a recent study, we have unequivocally demonstrated the profusion of candidal species in S-ECC [ 20 ]. Furthermore, the current consensus is that caries, in general, is not caused by specific organisms, such as Streptococcus mutans and lactobacilli, but by a polymicrobial consortium of cariogenic species.…”
Section: Introductionmentioning
confidence: 95%
“…In terms of the predominant microbiota of dental caries, both streptococcal and lactobacillus genera have long been recognized to play a critical role, although recent work indicates clearly that fungi, predominantly Candida species, are prevalent in deep cavitated lesions [ 18 , 19 ]. Indeed, in a recent study, we have unequivocally demonstrated the profusion of candidal species in S-ECC [ 20 ]. Furthermore, the current consensus is that caries, in general, is not caused by specific organisms, such as Streptococcus mutans and lactobacilli, but by a polymicrobial consortium of cariogenic species.…”
Section: Introductionmentioning
confidence: 95%
“…Both streptococci and lactobacilli have long been recognized to play a critical role in dental caries, although recent work indicates clearly that fungi, predominantly Candida species, play a critical role, particularly in the deep cavitated caries lesions [18]. Indeed, in a recent study, we have unequivocally demonstrated the profusion of candidal species in S-ECC [19]. Furthermore, the current consensus is that caries, in general, is not caused by speci c organisms, such as Streptococcus mutans and lactobacilli, but by a polymicrobial consortium of cariogenic species.…”
Section: Introductionmentioning
confidence: 69%
“…Although some pilot clinical studies with limited subjects did not observe significant differences in the prevalence of oral C. albicans between children with or without dental caries (9,10), multiple lines of evidence have shown that the presence of C. albicans in saliva and dental plaque is strongly associated with dental caries, especially ECC. In this regard, a number of cross-sectional studies have revealed that the prevalence of oral C. albicans in ECC children is significantly higher than that in caries-free children (4,(11)(12)(13)(14). In addition, several studies indicate that both the prevalence and carriage of oral C. albicans is positively correlated with the severity of ECC (12,(15)(16)(17).…”
Section: Albicans and Its Association With Eccmentioning
confidence: 99%
“…It was found that genotypes A, B, and C are typically detected in the dental plaque of children, genotype D is found in the periodontal pocket of patients with periodontitis, while genotype E is rarely present in the oral cavity (13). Others found that genotype A is mostly predominant in plaque biofilms of children with S-ECC, followed by genotypes C and B (11). In addition, genotype A was predominantly associated with proximal lesions, whereas genotypes B and C were mainly isolated from occlusal cavities.…”
Section: Albicans and Its Association With Eccmentioning
confidence: 99%
See 1 more Smart Citation